DEC2 Blocks the Effect of the ARNTL2/NPAS2 Dimer on the Expression of PER3 and DBP. (11th August 2017) - Olkkonen, Juri; Kouri, Vesa-Petteri; Kuusela, Elina; Ainola, Mari; Nordström, Dan; Eklund, Kari K.; Mandelin, Jami
The expression of clock genes ARNTL2, NPAS2 and DEC2 are disturbed in rheumatoid arthritis, an autoimmune disease with circadian variation of symptoms. We have shown that TNF is a potent inducer of these genes. We investigated the regulation of ARNTL2 and NPAS2 by TNF and elucidated their effect on other clock gene expressions. Additionally, we studied the effect of DEC1 and DEC2 on ARNTL, ARNTL2 and NPAS2 . Cultured primary human fibroblasts were stimulated with TNF and the effects on ARNTL2 and NPAS2 were studied with RT-qPCR and immunofluorescence staining. The role of NF-κB was analyzed using IKK-2 inhibitor IMD-0354. TNF promoted ARNTL2 localization into the nuclei. Similar to DEC2, the effects of TNF on ARNTL2 and NPAS2 expressions were mediated via NF-κB. Cloned ARNTL, ARNTL2, NPAS2, DEC1 and DEC2 were transfected into HEK293. The ARNTL2/NPAS2 dimer was a weaker inducer of PER3 and DBP than ARNTL/NPAS2. ARNTL2 and NPAS2 are regulated by TNF via the same mechanism as DEC2. Compared to their paralogs they have unique effects on other circadian components. Our data suggest that these genes are responsible, at least in fibroblasts, for the accurate adaptation of circadian timekeeping in individual cells during inflammation.